Aplikasi Smartphone untuk Pelaporan Gejala yang Dialami Pasien Kanker Anak - Ni Ketut Sri Armini; Sigit Mulyono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study was to describe the use of smartphones in reporting symptoms experienced by pediatric cancer patients. This research method uses a non-systematic literature review study method, looking for related articles from 2020-2022. The results obtained from ten associated journals and a review of the journals found that smartphones with various applications help report the condition of pediatric cancer patients and their daily experiences. In conclusion, all applications developed are acceptable and easy to use by patients, parents/caregivers, and health workers. Keywords: Game-Based Applications, Mobile Health Applications, Childhood Cancer, Smartphones